Study on surface properties of UHMWPE/Hap composite coating on Ti6Al4V. (3rd April 2022) - Çelebi Efe, Gözde; Yenilmez, Elif
ABSTRACT: In the present study, UHMWPE (Ultra High Molecular Weight Polyethylene)- 0.5, 1 and 2 wt-% Hap (hydroxyapatite) composite film coatings on Ti6Al4V alloy were produced by dip coating method. Homogeneous dispersion of Hap particles was detected by SEM (Scanning Electron Microscope) and FE-SEM (Field Emission Scanning Electron Microscope). The characteristic absorption peaks of Hap are observed by FTIR (Fourier Transform Infrared Spectroscopy). Hap addition caused the increment of the crystallinities of composites from 24.6% to 56.8% related with the increment of the melting temperatures. Composite coatings showed excellent wear resistance with the decreasing worn area of 96% and the friction coefficient of 97%, compared to the uncoated Ti6Al4V. The biocompatibility and wettability tests of all coated surfaces were performed. It is foreseen that UHMWPE/2wt-%Hap composite film coating on Ti6Al4V will be promising for Hip joint prosthesis.